Depersonalize and attack: facebook campaigns of populist candidates in Greece during the 2019 Greek national elections. Issue 1 (2nd January 2023) - Triantafillidou, Amalia; Lappas, Georgios
ABSTRACT: Using an actor-center approach, the present study sheds light on the intersection between populist communication and Facebook campaigns in the context of the 2019 general elections in Greece. Specifically, the study focuses on how populist actors in Greece campaigned on Facebook and examines their communicative performance in terms of user engagement in comparison with that of their opponents. For this purpose, a quantitative content analysis was performed by analyzing the Facebook posts published by populist and non-populist candidates over one week preceding the July 7 elections. Results suggest that candidates from populist parties, such as SYRIZA (Coalition of the Radical Left) and EL (Greek Solution), were outpaced by the mainstream New Democracy party that won the election. Moreover, significant differences are observed between populist and non-populist actors regarding the communication strategies utilized. Results suggest that different communication strategies have varying effects on user engagement depending on the populist identity of candidates, as well as their position in the left-right political spectrum. Several practical implications are proposed regarding the effective orchestration of Facebook campaigns by populist and non-populist actors.